Ceramic–polymer hybrid coatings for diverse applications - K R C, Soma Raju; R, Subasri; K, Srinivasa Rao (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
The sol–gel process is a simple wet chemical method used to generate nano-crystalline or nano-scaled amorphous ceramic and ceramic–polymer hybrid coatings. Pure ceramic and pure polymer coatings have certain limitations for use over a wide range of applications due to the high-temperature heat treatment requirement for the former and poor mechanical properties of the latter. Hence, ceramic–polymer hybrid coatings are the need of the hour for use in diverse applications on different substrates. Furthermore, bioinspired multifunctional coatings that mimic complex geometrics of the lotus leaf, pitcher plant, etc., are being investigated for their use in corrosion protection, biofilm inhibition, antifouling, etc. Such complex geometries can be generated by a combination of physical and chemical modifications of a surface. In the case of the chemical modification of a surface, instead of a pure ceramic or pure polymer coating, a ceramic–polymer hybrid coating would be the choice, as, a rigid backbone is provided by the ceramic (metal oxide network) moiety and a flexible structure by the polymeric moiety. This review discusses the sol–gel-derived pure ceramic and ceramic–polymer hybrid coatings, their applications, challenges, research gaps as they have been evolving over the years, and two nature-inspired phenomena, namely, superhydrophobicity and self-healing, that have been widely researched for use in various applications.